2021
DOI: 10.2147/idr.s296792
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Meningitis Among Adult Patients at University of Gondar Comprehensive Specialized Referral Hospital

Abstract: Background Bacterial meningitis is a bacterial infection that causes inflammation of the membranes that surround the brain and spinal cord. The most frequent causes of bacterial meningitis are Neisseria meningitidis, Streptococcus pneumoniae, Listeria monocytogenes , and Haemophilus influenzae . This study aimed to determine bacterial meningitis and their antibiotic susceptibility patterns among adult patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In a recent study, Tigabu and coworkers reported high resistance (66.80%) in S. aureus against erythromycin and amoxicillin among adult BM patients in Gondar. 42 Another study conducted by Assegu Fenta and his group declared that high resistance of S. aureus was reported against amoxicillin (100%). 43 The high resistance occurs due to exposure of broad range of antibiotics, self-medication, and incomplete dosage of antibiotics, leading S. aureus to develop new cellular processes to evade effects of drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Tigabu and coworkers reported high resistance (66.80%) in S. aureus against erythromycin and amoxicillin among adult BM patients in Gondar. 42 Another study conducted by Assegu Fenta and his group declared that high resistance of S. aureus was reported against amoxicillin (100%). 43 The high resistance occurs due to exposure of broad range of antibiotics, self-medication, and incomplete dosage of antibiotics, leading S. aureus to develop new cellular processes to evade effects of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…While Tigabu and group reported 100% susceptibility of N. meningitidis isolates against amoxicillin and erythromycin. 42 The variation in antibiotic susceptibility trend among isolates might be due to late diagnostic tests and misuse of antibiotics. Hence, the increasing antibiotic resistance among various pathogens is a serious health problem.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cases were probably misdiagnosed because of non-specific clinical presentation, physician behaviors, limited diagnostic capacity of the laboratory, and lack of surveillance for listeriosis. Studies have shown that blood or CSF cultures were often negative in these circumstances ( 10 , 11 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria and viruses are the most common causes of meningitis, but bacterial meningitis is usually severe and common. Accurate and timely identification of the etiological agents is vital to initiate public health measures and appropriate management (Tigabu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%